Readiness of Hospitality Management Students on their On-the-job Training - Joseph Famin; Maria Fe Factao; Martin Napalinga; Debbie Manalo; Ma. Ciaina Araneta; Marry Claire Faro (IC-ITECHS, 2022)
On-the-job training is one of the requirements for graduating students. This guides the students to identify their knowledge, competence, and readiness towards having their chosen field and specialization. The purpose of this study is to identify the level of readiness of fourth-year (4th) BS Hospitality Management students of Iloilo Science and Technology University—Miagao Campus during the first semester of the academic year 2021–2022. The study employed a descriptive survey method. Findings revealed that when taken as a whole, the respondents were partially ready for their internship. When classified, the findings revealed that there is no significant difference in the level of readiness of fourth (4th) Year BS Hospitality Management students as to class section and family monthly income, but a significant difference when it comes to sex and academic performance. Class section and family monthly income cannot affect their readiness for on-the-job training. Students can still be ready for his/her internship regardless of what group he/she belong to, and since the respondents are beneficiaries of a